Diagnóstico de los procesos de gestión pública de la Delegación Provincial del CNE - Martínez Andrade, Silvia Lisbeth (2023)
The objective of this study was to diagnose the public management processes of the Provincial Delegation of the National Electoral Council (CNE) of Cotopaxi. These processes are linked to institutional strategic planning and are subject to compliance with procedures for their execution. The problem of this research arises because many processes used by the entity are based on classic and bureaucratic models, which are rigid and not very dynamic. At present, state entities have a look towards the New Public Management (NGP), where there is greater citizen participation and innovation in order to reach the effectiveness of the public service. This diagnosis was made through the type of deductive research with a quantitative approach of a bibliographic nature through the application of surveys addressed to 384 users and 24 officials of the CNE of Cotopaxi, based on which the Chi Square hypothesis test was used. and it was determined that public management processes affect the performance of the Provincial Delegation, for which it is necessary to intensify the processes of training and dissemination of CNE services to society.